Catalytic hydrogenation of liquid alkenes with a silica-grafted hydride pincer iridium(iii) complex: support for a heterogeneous mechanism1. Issue 9 (17th September 2015) - Rimoldi, M.; Fodor, D.; van Bokhoven, J. A.; Mezzetti, A.
<x xml:space="preserve">Abstract</x> The silica-grafted Ir(iii) hydride complex [IrH(O–SBA-15)(POCOP)], prepared by treating [IrH2(O–SBA-15)] with SBA-15 (mesoporous silica), hydrogenates liquid alkenes at room temperature and under 1 atm H2 without leaching into solution.